Analisis Partisipasi Petani dalam Asuransi Pertanian - Ardiana, Mega Nabilla; Agusta, Ivanovich (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
Farmers participation is crucial for succeeding in the implementation of agricultural insurance in Indonesia. The purposes of this research are analyzing farmers' form and level of participation and also identifying some factors affecting farmer’s participation in agricultural insurance. The research was conducted in Curug Bitung Village, District of Nanggung, Bogor Regency involving 40 respondents. Primary data includes farmers characteristics, farmers participation form and farmers participation level as program beneficiaries. The data were processed using multivariable linear regression test. The results showed that the intensity of communication, age, education level, income level and length of stay did not significantly affect the participation level of farmers whose majority were at the level of no participation. Non-compliance occurs during program implementation. The form of participation shown by farmers in the program is varied.Keywords: agricultural insurance, internal and external factors, farmers' participation ABSTRAK Partisipasi petani menjadi hal yang penting dalam rangka menyukseskan penerapan asuransi pertanian di Indonesia. Tujuan penelitian ini adalah menganalisis bentuk dan tingkat partisipasi petani dalam asuransi pertanian serta mengidentifikasi faktor-faktor yang memengaruhi partisipasi petani dalam program asuransi pertanian. Penelitian dilakukan di Desa Curug Bitung, Kecamatan Nanggung, Kabupaten Bogor dengan melibatkan 40 responden. Data primer meliputi karakteristik petani, bentuk partisipasi petani dan tingkat partisipasi petani penerima program. Data diolah menggunakan uji regresi linier multivariable. Hasil penelitian menunjukkan intensitas komunikasi, usia, tingkat pendidikan, tingkat pendapatan dan lama tinggal tidak berpengaruh secara signifikan terhadap tingkat partisipasi petani yang mayoritas berada pada tingkatan tidak ada partisipasi. Ketidaksesuaian banyak terjadi selama penyelenggaraan program. Adapun bentuk partisipasi yang ditunjukkan petani dalam program bervariasi.Kata kunci: asuransi pertanian, faktor internal-eksternal, partisipasi petani